Real-Time Fatigue Mitigation with Air-Medical Personnel: The SleepTrackTXT2 Randomized Trial. (4th July 2019) - Patterson, P. Daniel; Moore, Charity G.; Guyette, Francis X.; Doman, Jack M.; Weaver, Matthew D.; Sequeira, Denisse J.; Werman, Howard A.; Swanson, Doug; Hostler, David; Lynch, Joshua; Russo, Lindsey; Hines, Linda; et al.
Abstract: Objective: The aims of this study were: 1) to determine the short-term impact of the SleepTrackTXT2 intervention on air-medical clinician fatigue during work shifts and 2) determine the longer-term impact on sleep quality over 120 days.Methods: We used a multi-site randomized controlled trial study design with a targeted enrollment of 100 (ClinicalTrials.gov NCT02783027). The intervention was behavioral (non-pharmacological) and participation was scheduled for 120 days. Participation was voluntary. All consented participants answered baseline as well as follow-up surveys. All participants answered text message queries, which assessed self-rated fatigue, sleepiness, concentration, recovery, and hours of sleep. Intervention participants received additional text messages with recommendations for behaviors that can mitigate fatigue. Intervention participants received weekly text messages that promoted sleep. Our analysis was guided by the intent-to-treat principle. For the long-term outcome of interest (sleep quality at 120 days), we used a two-sample t-test on the change in sleep quality to determine the intervention effect.Results: Eighty-three individuals were randomized and 2, 828 shifts documented (median shifts per participant =37, IQR 23–49). Seventy-one percent of individuals randomized (n = 59) participated up to the 120-day study period and 52% (n = 43) completed the follow-up survey. Of the 69, 530 text messages distributed, participants responded to 61, 571 (88.6%). Mean sleep quality at 120 days did not differ from baseline for intervention (p > 0.05) or control group participants (p > 0.05), and did not differ between groups (p > 0.05). There was no change from baseline to 120 days in the proportion with poor sleep quality in either group. Intra-shift fatigue increased (worsened) over the course of 12-hour shifts for participants in both study arms. Fatigue at the end of 12-hour shifts was higher among control group participants than participants in the intervention group (p < 0.05). Pre-shift hours of sleep were often less than 7 hours and did not differ between the groups over time.Conclusions: The SleepTrackTXT2 behavioral intervention showed a positive short-term impact on self-rated fatigue during 12-hour shifts, but did not impact longer duration shifts or have a longer-term impact on sleep quality among air-medical EMS clinicians.